External sensory-motor cues while managing unexpected slippages can violate the planar covariation law. (6th March 2019) - Aprigliano, F.; Monaco, V.; Micera, S.
Abstract: This study was aimed at investigating the intersegmental coordination of six older adults while managing unexpected slippages delivered during steady walking, and wearing an Active Pelvis Orthosis (APO). The APO was setup either to assist volunteers at the hip levels during balance loss or to be transparent. The Planar Covariation Law (PCL) of the lower limb elevation angles was the main tool used to assess the intersegmental coordination of both limbs (i.e., the perturbed and unperturbed ones). Results revealed that, after the onset of the perturbation, elevation angles of both limbs do not covary, a part from the robot-mediated assistance. These new evidences suggest that external sensory-motor cues can alter the temporal synchronization of elevation angles, thus violating the PCL.